Customary Rituals Influence of Adulthood on Successful Character Transformation of Youth in Pentecostal Churches in Migori County, Kenya - George Chacha; Dr. Regina Kinuthia; Dr. Kamwaria Alex (IJRDO - Journal of Social Science and Humanities Research, 2020)
Most of the Kurian Sub-tribe communities had always believed that rituals practices can sustain and improve the practices of succeeding traditional believes and customs which had not been confirmed. The purpose of this study was to analyze the influence of rituals on the character transformation of Christian youth a case of Pentecostal churches in Kuria West, Migori County. This study utilized the social action theory by Talcott Parson. Research Methodology was qualitative and quantitative while target population comprised of pastors, church leaders, youth leaders, church members and the youth in the selected Pentecostal churches in Kuria West Sub-county. Data was collected by use of Questionnaires for the youth, interview guides for pastors, church leaders, youth leaders, church members and focused group discussion for the youth. Random and stratified sampling was used. Data analysis was done by use of statistical package of social sciences (SPSS) The research findings were consistent all categories were interviewed where by the target group had 53% of the respondents the active age targeted for the traditional rituals 14-17yrs. The research findings were consistent whereby most respondents acknowledged that rite of passage had both positive and negative effects to the character transformation of Christian youths. It was also found that seminars, conferences and rallies are organized to pass the message of the effects of the rite of passage by the church leaders but it had yielded very little positive result towards the character transformation of youths. Youths had irregular attendance and were not actively participating towards the church programs developed. The five categories affirmed that the church has a role to teach the youth on the negative influence of traditional rituals as evidenced by 80% of the respondents who felt that Christian youth can be missionaries in a new way without leaving their land and reach more people than in traditional method. Therefore the findings of this study revealed that the youths to be taught by the church on the negative influence of traditional rituals to adulthood. The church leaders have a responsibility of educating the youth through seminars, rallies, and conferences as this will contribute to their character transformation.